THE The Effect of Telehealth-Based Self Management Interventions for Irritable Bowel Syndrome: A Systematic - Rofiqa Dwi Febriyanti; Ika Nur Pratiwi; Fayza Eka Zhafirah; Wynne Faiza Rosada (Indonesian Journal of Global Health Research, 2026)
An Irritable Bowel Syndrome (IBS) is a dysfunctional bowel disorder characterized by such gastrointestinal symptoms as abdominal pain, defecation, constipation, and bloating. Consequently, the condition may worsen over time. A systematic evaluation of the effectiveness, mechanisms, and implementation aspects of telemedicine-based self-management strategies in adults with irritable bowel syndrome (IBS). This study used a quantitative method with a systematic review approach following the PRISMA 2020 guidelines. The search was conducted in various databases such as PubMed, Scopus, Web Of Science (WOS), Sciencedirect, and Proquest with a publication year range from 2020 to 2025. The Boolean search strategy was: “self-management” OR “self-care” “telehealth” AND ‘telemedicine’ “Irritable Bowel Syndrome OR intestinal disorder.” From the 1,074 articles found, after screening using inclusion and exclusion criteria, 20 articles were selected for further analysis using the JBI Critical Appraisal checklist. 20 articles that met the study criteria showed that the use of telehealth can improve self-management skills and reduce the number of inpatient cases. The highest level of effectiveness was achieved through collaboration between telehealth and interprofessional health services in food map management. Digital self-management through telehealth is effective and feasible as an adjunct to IBS management, with consistent evidence for CBT-based, nutritional, relaxation, and multimodal interventions despite methodological variations.